Testing the Convergence Hypothesis in the European Union - MIHAELA SIMIONESCU (Global Economic Observer)
The main objective of this study is to measure the degree of convergence in European Union- 28 (EU-28) in the period from 1995 to 2012. The catch-up rates diminished for many countries in the period from 2008 to 2012, because of the negative effect of economic crisis, when the disparities among countries were larger. Three statistical tests were applied for the entire period and for the two sub-periods (1995-2007 and 2008-2012). All the statistics (T1, T2, and T3) values have indicated the existence of divergence in the EU-28 between the levels of GDP/capita in PPS. However, during the each analysed period there is an obvious decrease of the variance in the last period compared to the first period.